المصادر التاريخية لدراسة ظاهرة السكن العشوائي: المصادر التاريخية لدراسة ظاهرة السكن العشوائي - عناد وجدان فريق (مجلة دراسات في التاريخ والآثار, 2021)
الملخص : لا تخلو المصادر التاريخية من الإشارة إلى جذور معظم الظواهر الموجودة في الوقت الحاضر، وإن اختلفت التسمية من عصر إلى آخر، فمصطلح السكن العشوائي غير موجود في كتب التراث، ولكن الظاهرة موجودة وأشارت إليها المؤلفات التاريخية . Historical sources of study of the phenomenon of random housing Prof. Dr. Wijdan Fareeq Enad Revival of Arab Scientific Heritage Center Abstract The historical sources are not limited to reference to the roots of most of the phenomena that exist now, and that the name differed from one age to another. The term "random dwelling" was not used, but the phenomenon existed in the Islamic times and was referred to by the heritage books